Deep Digital Flexor Tendon Injury at the Level of the Proximal Phalanx in Frontlimbs With Tendon Sheath Distension Characterized by Standing Low-Field Magnetic Resonance Imaging in Horses: 13 Cases (2015–2021) - Elisabeth Cornelia Susanna van Veggel (Frontiers Media S.A., 2021)
Objective: To describe the MRI findings for 13 horses with deep digital flexor tendon (DDFT) injury at the proximal phalanx where the tendon goes from ovoid to bilobed in frontlimbs with tendon sheath distension. In addition, the prognosis of this lesion was assessed.Design: Retrospective case series.Animals: Thirteen client-owned horses.Procedures: Medical records were reviewed, and data were collected regarding signalment, history, MRI findings, and outcomes of horses. Findings of MRI were recorded and whether the case was confirmed with tenoscopy.Results: A diagnosis of DDFT injury at the junction between ovoid and bilobed portions at the level of the proximal phalanx was established in 13/20 (65%) horses that underwent MRI examination of the frontlimb digital flexor tendon sheath. Return to previous level of work was poor in this subset of horses with only three of 13 (23%) horses returning to previous level of work and one horse still in rehabilitation.Conclusions and Clinical Relevance: Standing low-field MRI represents a potentially useful diagnostic tool to evaluate digital flexor tendon sheath distension especially when evaluating the DDFT at the proximal phalanx where the tendon progresses from ovoid to bilobed. Prognosis of lesions of the DDFT at the proximal phalanx appears less favorable than previously reported causes of tendon sheath distension.